2017
DOI: 10.1111/jasp.12461
|View full text |Cite
|
Sign up to set email alerts
|

Sexualized images in professional contexts: Effects on anticipated experiences and perceived climate for women and men

Abstract: Academic conferences are important settings for socialization, scholarly engagement, and networking. Two studies explore the effects of ambient cues in such settings on women's and men's climate perceptions. Participants (undergraduates in Study 1, graduate students in Study 2) viewed a flyer advertising a professional mixer that included an eroticized image or a control image.Women and men expected a sexualized atmosphere, and women in particular anticipated lower feelings of competence and greater discomfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…However, particular types of jokes and behaviours (i.e., racialized, sexualized) are socially charged and carry loaded cues about belonging to a group. Such identity cues-"socially symbolic [objects] that embody and communicate group member stereotypes to others" (Cheryan et al 2009(Cheryan et al , p. 1046; see also Cheryan et al 2017)-can make some people feel uncomfortable, especially when they are already marginalized within a community (e.g., Biernat and Hawley 2017). We observed several of these types of identity cues in the 11 sessions that had no female presenters.…”
Section: Use Of Languagementioning
confidence: 75%
See 1 more Smart Citation
“…However, particular types of jokes and behaviours (i.e., racialized, sexualized) are socially charged and carry loaded cues about belonging to a group. Such identity cues-"socially symbolic [objects] that embody and communicate group member stereotypes to others" (Cheryan et al 2009(Cheryan et al , p. 1046; see also Cheryan et al 2017)-can make some people feel uncomfortable, especially when they are already marginalized within a community (e.g., Biernat and Hawley 2017). We observed several of these types of identity cues in the 11 sessions that had no female presenters.…”
Section: Use Of Languagementioning
confidence: 75%
“…This work has King et al the lack of representation of women and people of colour as invited speakers and argued that a more intentional approach to improving diversity in this domain would help to provide role models for minorities and broaden the concept of "ideal worker" in geoscience (see Holmes et al 2015b, p. 3) to include people of diverse backgrounds. Beyond geoscience, diversity scholars have shown that women often experience subtle forms of sexism and incivility at conferences (Settles and O'Connor 2014;Biernat and Hawley 2017;Biggs et al 2017), and that collectively these experiences affect women's intentions to pursue a career in their scientific field of interest (Ratliff 2012). Women of colour were found to be significantly more likely to miss professional events such as conferences because they feel unsafe, resulting in lost career opportunities (Clancy et al 2017).…”
Section: Introductionmentioning
confidence: 99%